COMPARATIVE STUDY OF PESANTREN-ENHANCED RELIGIOUS TOURISM IN WEST SUMATRA - Afrilian, Pepy; Yadno, M. Nur Abdul Endri (Fakultas Ekonomi dan Bisnis Islam - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: This study investigates the potential of religious tourism integrated with the pesantren experience, merging mosque visits with immersive santri life. The research objective is a comparative analysis of religious tourism packages based on the pesantren approach, encompassing itinerary design, budget planning, and evaluation of each package's efficacy and shortcomings. Employing qualitative methods, the study gathers data through repeated observations, semi-structured interviews, purposive sampling, and documentation. Data analysis involves thematic coding, comparative techniques, and triangulation of diverse data sources. Findings highlight the critical role of meticulous itinerary planning in crafting compelling religious tourism experiences that blend nature, culture, and Islamic history in Minangkabau. The Chaining Loop travel pattern enhances appeal by integrating various tourism activities, offering flexible packages for both individual tourists and groups. The study concludes that overly condensed religious tourism schedules are inadvisable, while extended durations pose logistical challenges for tourists. Financial insights underscore the necessity for strategic management of fixed and variable costs, demonstrating that the Chaining Loop approach can significantly optimize budget efficiency. Keywords: religious tourism; pesantren; tourism package; travel patterns. Abstrak: Penelitian ini dilatarbelakangi oleh potensi wisata religi dengan integrasi pesantren, yang menggabungkan kunjungan wisatawan ke berbagai masjid sekaligus mendalami pengalaman kehidupan santri. Tujuan penelitian ini adalah menganalisis komparasi perencanaan paket wisata religi dengan pendekatan pesantren, dimulai dari perencanaan perjalanan, penyusunan anggaran, serta analisis keberhasilan dan kegagalan masing-masing paket wisata. Metode kualitatif digunakan dalam penelitian ini, dengan teknik pengumpulan data melalui observasi berulang, wawancara semi-terstruktur, purposive sampling, dan dokumentasi. Analisis data dilakukan melalui proses pengkodean tematik, teknik membandingkan temuan, dan triangulasi berbagai sumber data. Temuan penelitian menunjukkan bahwa perencanaan perjalanan (Itinerary) sangat penting dalam proses perencanaan wisata religi berbasis pesantren, dengan menyusun perjalanan yang menggabungkan wisata alam, wisata budaya, serta sejarah Islam di daerah Minangkabau. Perencanaan perjalanan dengan konsep Chaining Loop membuat rangkaian perjalanan dengan kombinasi wisata lainnya menjadi menarik dan fleksibel untuk wisatawan, baik individu maupun kelompok. Penerapan wisata religi dengan durasi yang padat tidak direkomendasikan, sementara durasi yang panjang juga menyulitkan wisatawan dalam mencari waktu yang sesuai. Hasil temuan juga menunjukkan pentingnya manajemen dan pengelolaan anggaran fixed cost dan variable cost, di mana konsep Chaining Loop dapat meningkatkan efisiensi anggaran. Kata Kunci: wisata religi; pesantren; paket wisata; pola perjalanan.